Optimized MOL‐PCR for Characterization of Microbial Pathogens. Issue 1 (6th January 2016) - Wuyts, Véronique; Roosens, Nancy H.C.; Bertrand, Sophie; Marchal, Kathleen; De Keersmaecker, Sigrid C.J.
Abstract: Characterization of microbial pathogens is necessary for surveillance, outbreak detection, and tracing of outbreak sources. This unit describes a multiplex oligonucleotide ligation‐PCR (MOL‐PCR) optimized for characterization of microbial pathogens. With MOL‐PCR, different types of markers, like unique sequences, single‐nucleotide polymorphisms (SNPs) and indels, can be simultaneously analyzed in one assay. This assay consists of a multiplex ligation for detection of the markers, a singleplex PCR for signal amplification, and hybridization to MagPlex‐TAG beads for readout on a Luminex platform after fluorescent staining. The current protocol describes the MOL‐PCR, as well as methods for DNA isolation, probe design, and data interpretation and it is based on an optimized MOL‐PCR assay for subtyping of Salmonella Typhimurium. © 2016 by John Wiley & Sons, Inc.